Bibliometric analysis of research on the maize based on top papers during 2009-2019 - Yuan, Bao-Zhong; Sun, Jie (Collnet journal of scientometrics and information management, 2020)
Based on the Essential Science Indicators database, this study analyzed 1,016 top papers of maize or corn research from 2009 to 2019, which include 1,016 highly cited papers and 11 hot papers in the field. We analyze the top papers of scientific research on the maize in the Science Citation Index Expanded, focusing on productivity, subjects, institutions, citations, and trends, and mapped by VOSviewer. Results showed that all paper written in English, were from 4,619 authors, 1,327 organizations and 89 countries/territories, listed in 323 core journals. Top 5 core journals with higher impact factor ranked as Plant Physiology, PNAS, Food Chemistry, Bioresource Technology and Plant Cell. Top 5 countries and regions were USA, Peoples R China, Germany, England and Australia. Top 5 organizations were Cornell Univ, Chinese ACAD Sci, Univ Wisconsin, ARS and Univ Minnesota. Based on the analysis of network map of VOSviewer, there is cooperation for authors, organizations and countries or regions. The analysis of all keywords showed that maize and corn research were separated six clusters. In addition, this study demonstrates that there are more top papers come from journals with the higher IF and higher rank in WoS Category. Authors can choose their ideal journal with a high impact factor or Q1 in Category to publish their papers in the English language related to their research field.